2023
DOI: 10.1080/19420862.2023.2211185
|View full text |Cite
|
Sign up to set email alerts
|

High concentration formulation developability approaches and considerations

Abstract: The growing need for biologics to be administered subcutaneously and ocularly, coupled with certain indications requiring high doses, has resulted in an increase in drug substance (DS) and drug product (DP) protein concentrations. With this increase, more emphasis must be placed on identifying critical physico-chemical liabilities during drug development, including protein aggregation, precipitation, opalescence, particle formation, and high viscosity. Depending on the molecule, liabilities, and administration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 101 publications
0
13
0
Order By: Relevance
“…As industrial trends shift toward the use of high-concentration (>150 mg/mL) protein drugs to simplify drug administration and increase patient compliance, understanding interface-induced protein aggregation vs. aggregation in bulk solution will become even more critical. 15 This is because high-concentration formulations exhibit physicochemical properties that differ from dilute solutions, such as higher bulk viscosities and possible liquid−liquid phase separation. Also, the effects of intermolecular interactions in concentrated protein solutions are much more pronounced, which can exacerbate aggregation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As industrial trends shift toward the use of high-concentration (>150 mg/mL) protein drugs to simplify drug administration and increase patient compliance, understanding interface-induced protein aggregation vs. aggregation in bulk solution will become even more critical. 15 This is because high-concentration formulations exhibit physicochemical properties that differ from dilute solutions, such as higher bulk viscosities and possible liquid−liquid phase separation. Also, the effects of intermolecular interactions in concentrated protein solutions are much more pronounced, which can exacerbate aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the adsorption of protein molecules to interfaces can also lead to partial protein unfolding and interface-induced protein particle formation. , However, the mechanisms and variables involved in interface-induced protein aggregation are far less understood. As industrial trends shift toward the use of high-concentration (>150 mg/mL) protein drugs to simplify drug administration and increase patient compliance, understanding interface-induced protein aggregation vs. aggregation in bulk solution will become even more critical . This is because high-concentration formulations exhibit physicochemical properties that differ from dilute solutions, such as higher bulk viscosities and possible liquid–liquid phase separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our early research, along with that of peers, consistently reveals that while the addition of certain amino acids or inorganic salts can effectively lower the monoclonal antibody (mAb) solution’s viscosity, the extent of viscosity reduction varies. ,,, Some mAbs experience a substantial decrease in viscosity, whereas for others, the reduction in solution viscosity is not as pronounced. Currently, reduction of protein viscosity mainly relies on formulation optimization in a trial-and-error style . The intrinsic relationship between the protein structure and solution viscosity remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, reduction of protein viscosity mainly relies on formulation optimization in a trial-and-error style. 13 The intrinsic relationship between the protein structure and solution viscosity remains unknown. A deeper understanding of how protein characteristics, such as shape, surface charge distribution, molecular flexibility, etc., influence viscosity would inform the rational design of next-generation, high-concentration protein therapeutics.…”
Section: ■ Introductionmentioning
confidence: 99%